CHARACTERISTICS OF ADMINISTRATION OF COMMERCIAL BANKS' ASSETS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
In the thesis, the author commented on the asset operations of commercial banks, their management tools and methods, the main components of the asset management process, as well as the methods of investing funds.